Relative roles of wind, crop seeds, and cattle in the dispersal of Striga species - Berner, D.K.; Cardwell, K.; Faturoti, B.; Ikie, F.; Williams, O. (Scientific Societies, 1994)
In field trials conducted in Nigeria during 1991-92, the factors affecting the seed dispersal of Striga spp. were evaluated. Petrolatum-coated microscope slides placed at regular intervals from S. hermonthica plants and suspended from trees at 1-, 2- and 3-m above-ground heights within and around infested fields indicated that distribution of seeds of this weed by wind was not extensive. The max. horizontal distance away from S. hermonthica plants that seeds were caught was 12 m, and the max. vertical distance was 2 m. Samples of local market supplies of cowpeas, maize, millets and sorghum from 6 areas of Nigeria were found to contain Striga spp. seeds. Cattle dung was also sampled for the presence of Striga spp. seeds in 45 locations (88 fields) in S. hermonthica-infested areas of Nigeria. It was concluded that cattle dung was of minor importance in seed dispersal. Implications of dispersal mechanisms in control are discussed.